The Scene of Linguistic Action and its Perspectivization by SPEAK, TALK, SAY and TELL. - Dirven, René (Pragmatics & beyond, 1982)
The four papers presented in this volume are corpus-based investigations into the meaning of the verbs speak, talk, say and tell. More specifically they want to explore how the scene of linguistic action has been put into perspective by these four high-frequency verbs.